Technology for civilian self-protection. - Kaplan, Oliver; Rhoads, Emily Paddon (International Affairs, 2025)
From alerting communities at risk to connecting local responders to those in need, information and communication technologies (ICTs) are transforming local protective responses in contexts of armed conflict. While scholars have analysed how state and non-state armed groups' use of social media and ICTs shapes conflict dynamics, the protective application of technology by communities themselves to avoid harm remains underexplored and undertheorized. This article maps the range of existing and emerging technologies that individuals and communities harness for their own protection—for 'civilian self-protection'. It develops a theory and identifies the causal mechanisms through which ICTs may augment civilians' capacities for self-protection. The analysis finds that civilians' use of technology is vast, and ICTs are being adapted for protection in novel ways. These technologies and mechanisms are explored through two case-studies based on original interviews, relating to the non-violent civilian movements of the Indigenous Guard in Colombia and the White Helmets in Syria. The cases indicate that certain ICTs can amplify existing (low-tech) non-violent protective actions, such as by increasing the effectiveness of community coordination, 'naming and shaming' and early warning systems. ICTs also enable new actions and approaches that are simply not possible without the technology in hand, such as countering disinformation. While new technologies may strengthen local/international protection partnerships and bolster the agency of vulnerable groups, technology can also exacerbate existing protection challenges and create new ones.